Biochemical Profile of Amniotic and Allantoic Fluid During Different Gestational Phases in Mares - Zanella, Luiz Francisco; Takahira, Regina Kiomi [UNESP]; Melo e Oña, Cely Marini; Oña Magalhães, Luis Carlos; Prestes, Nereu Carlos [UNESP] (Elsevier, 2013)
Fetal fluids have different vital functions that sustain both pregnancy and normal parturition. The biochemical composition of amniotic fluid during gestation is not well established; thus the purpose of the present study was to determine the biochemical profile of both amniotic and allantoic fluids from mares during initial, mid, and latter third phases of pregnancy. Samples were collected after slaughter, using allantocentesis and amniocentesis. Sixty samples of fetal fluids were analyzed. Alkaline phosphatase (AP), glucose, total protein (TP), urea, creatinine, Ca, chloride (Cl), Na, and K concentrations were measured using commercially available kits. The AP concentration in amniotic fluid was higher than that in allantoic fluid during the three gestational phases (P < .05). There were no differences between glucose mean values of allantoic and those of amniotic fluids (P < .05). However, glucose values were higher in the allantoic fluid in the last trimester of pregnancy. TP was higher in the amniotic fluid than in allantoic fluid (P < .05). Urea values varied among the phases; however, there were no differences between the amniotic and allantoic fluid values (P > .05). Creatinine values were higher in allantoic fluid (P < .05). Na and Cl concentrations were higher in amniotic fluid (P < .05). However, Ca and K concentrations were higher in the allantoic fluid. © 2013 Elsevier Inc. All rights reserved.
Keywords: Alkaline phosphatase; Allantoic fluid; Amniotic fluid; Mare; Sodium; Total protein